EVALUASI PEMBELAJARAN DI PONDOK PESANTREN BALI BINA INSANI TABANAN BALI - Aini, Evva; Sukmawati, Nur Ika; Nurfalahsyifa, Mutia; Mawadah, Fina; Fadhillah, Ayu; Nafi’, Fajar Ilman (Jurnal Al Burhan, 2024)
This research aims to explore and analyze the learning evaluation methods used at the Bali Bina Insani Islamic Boarding School. This research used  qualitative research methods with field research, as well as data collection techniques through observation, interviews, and documentation. The results of this research indicated that the Bali Bina Insani Islamic Boarding School applied several conventional evaluation systems that have been modified based on existing local conditions. First, Evaluation of Bahtsul Kutub (Muwajjahah) for developing critical thinking skills in understanding the book. Second, Evaluation of Amaliyah Worship Practices which emphasizes the element of spirituality in the form of worship practices. Third, oral examinations to evaluate students' memorization of religious and general knowledge. Fourth, written examinations that are relevant to the material previously taught to measure the students' abilities and comprehension. All assessment implementations are supported by a conducive learning environment, adequate facilities, and high integrity of educators, ensuring that the learning assessment process can run effectively and is able to improve the quality of students who are adept in a multicultural Islamic education environment.